Diagnosis, classification and monitoring of leukemia based on Raman spectroscopy (Research, Society and Development, 2021)
The diagnosis, classification and monitoring of leukemia requires the use and combination of various technologies usually involving staining and examining the morphology of cells in a blood sample or selective detection of specific cell membrane antigens. Raman spectroscopy is an optical technique based on the inelastic scattering of light by molecules and can provide highly specific biochemical information with minimal or no sample pretreatment. Based on this, the present study aimed to carry out a systematic review through the survey of peaks and markers in experimental and clinical studies about the use of Raman spectroscopy in the diagnosis and classification of leukemia. With the analysis of the selected studies, it was possible to show great progress in research on the applicability of Raman spectroscopy in diagnosis, in particular on its specificity and sensitivity, to ensure the differentiation between the four main subtypes of leukemia: chronic lymphoid leukemia (CLL), acute lymphoid leukemia (ALL), chronic myeloid leukemia (CML) and acute myeloid leukemia (AML).